Penerapan Metode Design Thinking dan Agile dalam Rancang Bangun Aplikasi Penjualanku - Zaid Amin; Nabila Pasha (Journal of Information System Research (JOSH), 2023)
Design thinking is a method that concentrates on generating ideas and solutions that begin with a process of empathy for a need that focuses on a human or user perspective. The stages of design thinking can be done repeatedly to improvise ideas and solutions so that they are responsive and adaptive to change. Agile is a software development method in which the stages can be repeated to form a cycle, this is done because the agile method is very concerned about the value of a product. The Anindya Collection is UMK of men's batik clothing that they produce themselves and sell under their own business brand name, Anindya Collection. Problems often occur in managing sales data and recapitulating sales data which is still done manually, namely handwriting in a book, making it less effective and efficient. UMK has a role in boosting the Indonesian economy, so limitations should not prevent UMK from innovating. In this study the authors implemented the Design thinking and Agile Methods in Designing the My Sales Application at Anindya Collection). In this study, the authors concluded that the design thinking method helps improvise ideas and solutions to changes prior to the development stage using agile methods. Meanwhile, agile methods help implement ideas and solutions generated from the design thinking stage.